ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASING DI RUMAH SAKIT UMUM DAERAH PAMEUNGPEUK KABUPATEN GARUT - Eny Nuryani (KarismaPro, 2020)
The background of this research is the factors that influence buying (purchasing) the people coming for treatment to hospitals Pameungpeuk. This study aims to determine the most dominant factor affecting the purchasing public to come for treatment to hospitals Pameungpeuk. The research method used in this research is descriptive method of analysis. The study population were people who came for treatment to the hospital during the study. Data collection was done by literature study, observation and questionnaires. The data obtained were then analyzed using descriptive analysis techniques to test factor analysis.The results showed that in general, all of these factors affect the purchasing public as seen in the table component testing matric have values above the standard value of the factor analysis is 0.5, where the factor price policy dominant influence purchasing community because the value of its largest component matrix of factor another is 0.877. The suggestions can be put forward is expected to hospital administrators realize Pameungpeuk deepest problems increased purchasing public, considering the price variable has the most dominant influence on purchasing in hospitals Pameungpeuk, so hopefully the board can maintain pricing policy and consider factors that can increase purchasing such researchers discovered a new factor which factors increase the public purchasing.